Immune status of dairy calves in the Northern Plains of Costa Rica. Year II. - Benavides-Varela, Daniel (2013)
The objective of this study was to characterize for the second consecutive year the immune status of dairy calves in the Northern Plains of Costa Rica. The data correspond to total serum protein measurements obtained during the period of August and November 2011 in 33 dairy farms. Dam breeds were classified as Holstein, Jersey, HolsteinxJersey crosses, and others. For the purpose of this study, failure of passive immunity was considered when TSP concentration was less than 5.5 g/dl. TSP concentration ranged from 2.0 to 10.0, with an overall mean of 5.7 g/dl. Of the animals evaluated, 43.7% had failure of passive transfer. When sex of the calves was considered, 44.1% of females and 38.3% of males failed to obtain adequate levels of immunity and concentration of TSP showed no significant differences (6.0 vs. 6.1 g/dl). Calves born to HolsteinxJersey crosses had significantly higher TSP concentrations than calves born to other breeds. When considering calving of the dam, offsprings born to first time heifers had TSP concentrations of 6.3 g/dl and showed the lowest percentage of animals with inadequate transfer of immunity. The findings of this study suggest that colostrum management practices should be placed in order to minimize the risk of failure of passive transfer in dairy herds in the Northern Plains of Costa Rica.